Investigation of GPR137C as a promising novel marker for the progression of prostate cancer through G4 screen and bioinformatics analyses - Hou, Yue; Lu, Haowen; Chen, Saisai; Mao, Likai; Huang, Xuan; Xu, Feng; Shu, Chuanjun (Frontiers in Immunology, 2025)
IntroductionProstate cancer (PCa) remains the fifth leading cause of male cancer mortality, necessitating novel biomarkers and therapeutic targets.MethodsThrough BG4 ChIP-seq profiling in PCa cells, we identified promoter G-quadruplex (G4) structures in prognosis-associated genes, with GPR137C exhibiting a functional G4 in its promoter.ResultsThis G4 structure facilitates promoter hypomethylation to activate GPR137C transcription. Moreover, GPR137C promotes tumor microenvironment remodeling by enhancing immune cell infiltration, thereby driving PCa progression.DisscussionThis study establishes promoter G4s as epigenetic regulators in PCa while proposing GPR137C as both a prognostic biomarker and a therapeutic nexus for GPCR-targeted drug development.